(untitled) (Medicine Today, 2025)
Introduction: The outcome of open Achilles tendon injury is always challenging, primary repair is considered as gold standard procedure for open Tendo Achilles injury. Objective: To assess the outcome of primary repair within 24 hours of open Tendo Achilles injury. Materials and Methods: This prospective observational study was carried out among 50 patients attending at the Department of Orthopaedics, Comilla Medical College Hospital, Cumilla within the defined period from January 2022 to December 2022. Ethical clearance was obtained from the Institutional Review Board (IRB) of Comilla Medical College Hospital. Purposive sampling was done according to availability of the patients. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20.1). Evaluation was done according to Juhana Leppilahti’s modified scoring scale. Results: The mean age of the patients were 29.48 years with standard deviation of 13.53 years. More than two-thirds of the patients 34(68.0%) were male, whereas 16 (32.0%) were female. The majority of patients 30(60.0%) underwent surgery within 6-12 hours of injury. Moreover, half of the patients 28(56.0%) had been followed up for more than 6 months. According to Juhana Leppilahti’s modified scoring scale, mild pain was found in 26 patients 52.0%) and no pain in 24 patients (48.0%). Mild stiffness was found in 46 patients (92.0%), moderate in 1 patient (2.0%) and no stiffness was found in 3 patients (6.0%). Mild calf muscle weakness was found in 11 patients (22.0%). Mild footwear restrictions were found in 3 patients (6.0%). Half of the patients (n=25, 50.0%) had normal ROM (Range of motion) difference between affected and normal ankle after operation, 24 patients (48.0%) had mild ROM difference and 1 patients (2.0%) had moderate ROM difference. Almost half (n=24, 48.0%) of the patients had MRC grade 5, 20 patients (40.0%) had 4 MRC grade and 6 patients (12.0%) had 3 MRC grade. Subjective results very satisfied was found in 36 patients (72.0%), satisfied with minor reservations was in 13 patients (26.0%) and satisfied with major reservations was in 1 patients (2.0%). Conclusion: The present study suggests that primary repair within 24 hours of open Tendo Achilles injury is a safe and effective procedure with low complication rates. The majority of patients reported high levels of satisfaction with the procedure, and excellent to good outcomes were achieved in most cases. Medicine Today 2025, Vol.37 (1): 83-87